Sinus of Valsalva Rupture or VSD Shunt: Mystery Solved by Cardiac CT - Vora, Keyur; Surana, Uday; Ranjan, Alok (Indian Journal of Radiology and Imaging, 2021)
Unruptured aneurysm of sinus of Valsalva is an asymptomatic pathology and diagnosed incidentally. This extremely rare anomaly can be associated with other congenital cardiac anomalies which can make the diagnosis and prognosis even more complex. We are reporting a case of a 12-year-old boy with progressive dyspnea and episodes of syncope. Multimodality imaging confirmed the diagnosis and paved the way for appropriate surgical treatment options.
Keywords: cardiac CT; sinus of Valsalva aneurysm; surgical plan; ventricular septal defect